2013
DOI: 10.4103/0976-9668.107293
|View full text |Cite
|
Sign up to set email alerts
|

The study of the effects of ionizing and non-ionizing radiations on birth weight of newborns to exposed mothers

Abstract: Objectives:Life evolved in an environment filled with a wide variety of ionizing and non-ionizing radiation. It was previously reported that medical exposures to pregnant women increases the risk of low birth weight. This study intends to investigate the relationship between exposure to ionizing and non-ionizing radiation and the risk of low birth weight.Materials and Methods:One thousand two hundred mothers with their first-term labor (vaginal or cesarean) whose newborns’ history had been registered in neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 24 publications
(28 reference statements)
1
29
1
Order By: Relevance
“…Mortazavi et al examined using a large sample size of 1200 newborns, whose mothers had been either exposed or not exposed to dental radiography in Iran. It was shown that the children of mothers who had received dental radiography during their pregnancy showed no significant decrease in their birth weight (Mortazavi et al 2013).…”
Section: Examinationmentioning
confidence: 99%
“…Mortazavi et al examined using a large sample size of 1200 newborns, whose mothers had been either exposed or not exposed to dental radiography in Iran. It was shown that the children of mothers who had received dental radiography during their pregnancy showed no significant decrease in their birth weight (Mortazavi et al 2013).…”
Section: Examinationmentioning
confidence: 99%
“…Nevertheless, the question whether ionizing radiation exposure of future parents or peri-conceptional and embryonic radiation exposure impair fetal and post-natal development remains a controversial issue. There are articles in favor of and against this hypothesis, e.g., [54,55]. One problem with statistically negative studies in the clinical setting is sample size -typically in the range of only a few thousand [55] or below.…”
Section: Our Investigation Disclosed a Positive Association Between Tmentioning
confidence: 99%
“…Experimental and clinical studies indicate that various pathological conditions, including fetal loss, prenatal growth restriction, preterm birth, birth defects and behavior deficits, are associated with fetal exposure to environmental contaminants (Adams, 1989;Wigle et al, 2008;Au, 2010;Mortazavi et al, 2013). Chemical toxicants in air, water and foods, and various consumer products are some of the most important such contaminants (Wigle et al, 2008).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Mobile phones and health problems they may cause are therefore the subject of intense research among scientists (Barcal and Vozeh, 2007;Odaci et al, 2008;Wigle et al, 2008;Bas et al, 2009a;2009b;Sonmez et al, 2010;Feychting, 2011). Studies have reported, for instance, that high-frequency EMF damages sleep quality (Borbely et al, 1999), may lead to low birth weights (Mortazavi et al, 2013), and to behavioral disorders in children (Divan et al, 2008) and young people (Divan et al, 2012) and may cause headache in children (Sudan et al, 2012) and adults (Frey, 1998).…”
mentioning
confidence: 99%